Reduced Feeding Frequency Improves Feed Efficiency Associated With Altered Fecal Microbiota and Bile Acid Composition in Pigs - Yan, Honglin; Wei, Wenzhuo; Hu, Luga; Zhang, Yong; Zhang, Hongfu; Liu, Jingbo (Frontiers in Microbiology, 2021)
Bi-phasic feeding regimen exerts an improvement effect on feed efficiency of pigs. While gut microbiome and metabolome are known to affect the host phenotype, so far the effects of reduced feeding frequency on fecal microbiota and their metabolism of pigs remain unclear. Here, the combination of 16S rRNA sequencing technique as well as untargeted and targeted metabolome analyses were adopted to investigate the fecal microbiome and metabolome of growing-finishing pigs in response to bi-phasic feeding (M2) pattern. Sixty crossbred barrows were randomly assigned into two groups with ten replicates (3 pigs/pen), namely, the free-access feeding group (FA) and M2 group. Pigs in the FA group were fed free access while the M2 group were fed ad libitum twice daily for one hour at 8:00 and 18:00. Results showed that pigs fed bi-phasicly exhibited increased feed efficiency compared to FA pigs. The Shannon and simpson indexes were significantly increased by reducing feeding frequency. In the bi-phasic-fed pigs, the relative abundance of Subdoligranulum, Roseburia, Mitsuokella, and Terrisporobacter were significantly increased while the relative abundances of unidentified_Spirochaetaceae, Methanobrevibacter, unidentified_Bacteroidales, Alloprevotella, Parabacteroides and Bacteroides were significantly decreased compared to FA pigs. PLS-DA analysis revealed an obvious variation between the FA and M2 groups, the differential features were mainly involved in arginine, proline, glycine, serine, threonine, and tryptophan metabolism as well as primary bile acid biosynthesis. In addition, the changes in the microbial genera were correlated with the differential fecal metabolites. Bi-phasic feeding regimen significantly increased the abundances of primary bile acids and secondary bile acids in feces of pigs, and the differential enriched bile acids were positively correlated with some specific genera. Taken together, these results suggest that the improvement effect of reduced feeding frequency on feed efficiency of pigs might be associated with the altered fecal microbial composition and fecal metabolite profile in particular to enlarged stool bile acids pool.